Evaluation of a Re-designed Framework for Embodied Cognition Math Games - Casano, Jonathan D L (Archīum Ateneo, 2019)
Embodied cognition posits that the development of thinking skills is distributed among mind, senses, and the environment. Research in this field has resulted into the development of applications in different areas including mathematics. This paper reports one part of a larger series of studies on the design and implementation of embodied cognition-based mathematics educational systems. We describe the evaluation of a game called Estimate It!, a wearable-based game for teaching measurement estimation and geometry. Experts were invited to evaluate the game, resulting in a generally positive rating. The game’s collaborative nature, its hands-on way of teaching estimation, and the incorporation of technology were seen as promising points. Infrastructure readiness, classroom control, and adjustment to the new technology were areas of concern.